The innate face of Giant Cell Arteritis: Insight into cellular and molecular innate immunity pathways to unravel new possible biomarkers of disease - Rizzo, Chiara; La Barbera, Lidia; Miceli, Giuseppe; Tuttolomondo, Antonino; Guggino, Giuliana (Frontiers in Molecular Medicine, 2022)
Giant cell arteritis (GCA) is an inflammatory chronic disease mainly occurring in elderly individuals. The pathogenesis of GCA is still far from being completely elucidated. However, in susceptible arteries, an aberrant immune system activation drives the occurrence of vascular remodeling which is mainly characterized by intimal hyperplasia and luminal obstruction. Vascular damage leads to ischemic manifestations involving extra-cranial branches of carotid arteries, mostly temporal arteries, and aorta. Classically, GCA was considered a pathological process resulting from the interaction between an unknown environmental trigger, such as an infectious agent, with local dendritic cells (DCs), activated CD4 T cells and effector macrophages. In the last years, the complexity of GCA has been underlined by robust evidence suggesting that several cell subsets belonging to the innate immunity can contribute to disease development and progression. Specifically, a role in driving tissue damage and adaptive immunity activation was described for dendritic cells (DCs), monocytes and macrophages, mast cells, neutrophils and wall components, such as endothelial cells (ECs) and vascular smooth muscle cells (VSMCs). In this regard, molecular pathways related to cytokines, chemokines, growth factors, vasoactive molecules and reactive oxygen species may contribute to the inflammatory process underlying GCA. Altogether, innate cellular and molecular pathways may clarify many pathogenetic aspects of the disease, paving the way for the identification of new biomarkers and for the development of new treatment targets for GCA. This review aims to deeply dissect past and new evidence on the innate immunological disruption behind GCA providing a comprehensive description of disease development from the innate perspective.